1997
DOI: 10.1016/s0194-5998(97)70238-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Head and Neck Cancer Patients: Zinc Status and Immunologic Functions

Abstract: In this study we have assessed zinc status and zinc-dependent cell-mediated immune functions (interleukin-2 production by mononuclear cells, natural killer cell lytic activity, and interleukin-1 beta production by mononuclear cells) in adult patients with squamous cell carcinoma of the upper aerodigestive tract at diagnosis and before any therapy was instituted. Inasmuch as significant interactions between zinc, copper, and iron exist, we also assayed the plasma copper level, serum iron level, and total iron-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Significant depletion in Zn concentration in both the two groups of patients suffering from oral premalignant disorders might be considered as a vicious cycle, where decrease in Zn concentration as a consequence of the disorders could be a risk factor to predispose the individuals to further progression of the disease towards cancer [19,20]. Other researchers also reported that zinc deficiency and zinc-dependent immunologic dysfunctions are present in more than half of the patients with head and neck cancer [21]. As both OSF and leukoplakia involve inflammatory processes, it may be inferred that prolonged inflammation due to such lesions induces oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…Significant depletion in Zn concentration in both the two groups of patients suffering from oral premalignant disorders might be considered as a vicious cycle, where decrease in Zn concentration as a consequence of the disorders could be a risk factor to predispose the individuals to further progression of the disease towards cancer [19,20]. Other researchers also reported that zinc deficiency and zinc-dependent immunologic dysfunctions are present in more than half of the patients with head and neck cancer [21]. As both OSF and leukoplakia involve inflammatory processes, it may be inferred that prolonged inflammation due to such lesions induces oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…We were unable to determine exactly whether our patients had mild zinc deficiency or not. Furthermore, the studies of Prasad (43,44) confirmed that the measurement of zinc levels in lymphocytes and granulocytes is a more sensitive indicator of mild zinc deficiency in humans. The criteria they established for diagnosing mild zinc deficiency were lymphocyte zinc level 50/mg/10 10 cells and granulocyte zinc level 42/mg/10 10 cells.…”
Section: Effects On Overall Survival and Progression-free Survivalmentioning
confidence: 90%
“…Each person has a serum that contains a unique concentration of different substances: e.g., hormones [19], trace elements [24], immune complexes [32], colonystimulating factors [34], interleukins [4]. Since the responsiveness of monocytes is dependent on the concentration of these substances, it is of interest to study monocyte function as close to the in vivo condition as possible.…”
Section: Introductionmentioning
confidence: 99%